2018
DOI: 10.1088/1361-665x/aac362
|View full text |Cite
|
Sign up to set email alerts
|

Ship-bridge collision monitoring system based on flexible quantum tunneling composite with cushioning capability

Abstract: In this paper, a ship-bridge collision monitoring system based on flexible quantum tunneling composite (QTC) with cushioning capability is proposed by investigating the sensing capability and positioning capability of QTC to collisions. QTCs with different rubber matrix and thickness were fabricated, and collision tests between steel ball and QTCs sensors were designed to simulate ship-bridge collision. The results show that QTCs have a sensing range over 50 MPa with stress resolution ranging between 0.017 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Because of the quality gap of the homemade sensors, the sensor output showed a lack of consistency due to impact energy level, but it was apparent that the sensors showed fairly linear impact responses to changes in both impact energy and distance. We compared the impact sensing properties of nano carbon composite sensors with another piezoresistive impact sensor made of nickel powder composites [52]. The nickel powder composite impact sensor also showed fairly good impact responses with consistency but the sensitivity could not be compared due to lack of information on the study.…”
Section: Impact Sensing Resultsmentioning
confidence: 99%
“…Because of the quality gap of the homemade sensors, the sensor output showed a lack of consistency due to impact energy level, but it was apparent that the sensors showed fairly linear impact responses to changes in both impact energy and distance. We compared the impact sensing properties of nano carbon composite sensors with another piezoresistive impact sensor made of nickel powder composites [52]. The nickel powder composite impact sensor also showed fairly good impact responses with consistency but the sensitivity could not be compared due to lack of information on the study.…”
Section: Impact Sensing Resultsmentioning
confidence: 99%
“…A composite is produced from two or more constituent materials to achieve better performance than individual components [ 1 ]. They are classified into four categories based on the matrix constituent, such as (a) polymer matrix composites, (b) metal matrix composites, (c) ceramic matrix composites, and (d) quantum tunneling composites [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Quantum tunneling composites (QTCs) are combinations of polymer composites having both dielectric elastomer and conductive metal particles.…”
Section: Introductionmentioning
confidence: 99%
“…Within the finished structure of QTC, the individual elements remain separate and unique, distinguishing composites from mixtures and solid solutions. QTCs are demonstrated to use different applications, such as smart textiles, foot wears, touch pads, display devices, NASA’s Robonaut, mp3 players, sporting materials, automotive, and life science applications, such as measuring blood pressure, making safe batteries, and extreme weather conditions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The QTC pills for such applications were generally made using primarily silicone as a non-conductive elastomer and Nickel as one of the conductive materials.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced structural health monitoring system using stream processing and artificial neural network techniques (SPANNeT) is developed by Khemapech et al [ 12 ] for wireless sensor networks to enable real-time data streaming and proper damage detection under impacts, which, however, does not address the constraints of battery power limits for long-term deployment. Zheng et al [ 13 ] proposed a flexible quantum tunneling composite with cushioning capability for ship-bridge collision monitoring, and simple rule-based conditions are used for damage warning. A wireless transmission system is planned for future study but has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%